2021
DOI: 10.48550/arxiv.2112.00027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

H-alpha emission in local galaxies: star formation, time variability and the diffuse ionized gas

Sandro Tacchella,
Aaron Smith,
Rahul Kannan
et al.

Abstract: The nebular recombination line H๐›ผ is widely used as a star-formation rate (SFR) indicator in the local and high-redshift Universe. We present a detailed H๐›ผ radiative transfer study of high-resolution isolated Milky-Way and Large Magellanic Cloud simulations that include radiative transfer, non-equilibrium thermochemistry, and dust evolution. We focus on the spatial morphology and temporal variability of the H๐›ผ emission, and its connection to the underlying gas and star formation properties. The H๐›ผ and H๐›ฝ … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 125 publications
(171 reference statements)
2
6
0
Order By: Relevance
“…Keeping this in mind, our estimates are roughly consistent with other post-processing results from simulations with a multiphase ISM (e.g. Kado-Fong et al 2020;Smith et al 2021;Tacchella et al 2021).…”
Section: Dust Absorptionsupporting
confidence: 89%
“…Keeping this in mind, our estimates are roughly consistent with other post-processing results from simulations with a multiphase ISM (e.g. Kado-Fong et al 2020;Smith et al 2021;Tacchella et al 2021).…”
Section: Dust Absorptionsupporting
confidence: 89%
“…Similarly, the calibration shifts when varying between a Salpeter, Kroupa, and Chabrier IMF. Furthermore, Tacchella et al (2021) recently showed that additional corrections to standard scaling relations are needed for the absorption of Lyman continuum photons by dust and helium. Since simulations, in principle, can capture many (but not all) of these effects, we argue that they can be used to calibrate SFR-line luminosity relations.…”
Section: Star Formation Rate Indicatorsmentioning
confidence: 99%
“…One of these is the absorption of LyC radiation by dust: dust can absorb the LyC photons before they can ionise the hydrogen atoms, and re-emit them at longer wavelength. The typical fraction of LyC radiation absorbed by dust has been constrained to be of the order of 30 -50% in observations of nearby galaxies (Inoue et al 2001;Hirashita et al 2003;Iglesias-Pรกramo et al 2004;Salim et al 2016) as well as in simulations (Tacchella et al 2022).…”
Section: Photoionisation Budgetmentioning
confidence: 99%
“…There, ฮฃ mol was derived from CO line intensity with a radially varying CO-to-H 2 conversion factor (following Sun et al 2020). A stellar mass surface density ฮฃ โ‹† was derived from 3.6 ยตm SB with a varying stellar mass-to-light ratio (following Leroy et al 2021b), and then it was converted to ฯ โ‹† with an estimated stellar disk scale height from the disk radial scale length H โ‹† = R โ‹† /7.3 (van der Kruit & Searle 1981;Sun et al 2020). A fixed gas velocity dispersion of ฯƒ gas, z = 10 km s โˆ’1 was adopted following Leroy et al (2008).…”
Section: Pressure Terms As Function Of Galactocentric Radiusmentioning
confidence: 99%